COLLABORATION OF FUZZY LOGIC AND NEURAL NETWORKS - Marchuk, Dmytro; Kravchenko, Svitlana; Levkivskyi, Vitalii; Marchuk, G.V. (SWorld-Ger Conference proceedings, 2023)
The work considers the collaboration of fuzzy logic and neural networks. Based on the results of the study, the main types of neuro-fuzzy networks are identified. The hybrid model - ANFIS, its structural elements and mathematical model are considered. The